Electromagnetic information transfer through aqueous system. (3rd July 2017) - Foletti, Alberto; Ledda, Mario; Lolli, Maria Grazia; Grimaldi, Settimio; Lisi, Antonella
ABSTRACT: Several beneficial effects of the electromagnetic information transfer through aqueous system (EMITTAS) procedure have previously been reported in vitro . The clinical potential of this procedure has also started to be evaluated. Information flow in biological systems can be investigated through chemical and molecular approaches or by a biophysical approach focused on endogenous electrodynamic activities. Electromagnetic signals are endogenously generated at different levels of the biological organization and, likely, play an active role in synchronizing internal cell function or local/systemic adaptive response. Consequently, each adaptive response can be described by its specific electromagnetic pattern and, therefore, correlates with a unique and specific electromagnetic signature. A biophysical procedure synchronously integrating the EMITTAS procedure has already been applied for the treatment of articular pain, low-back pain, neck pain and mobility, fluctuating asymmetry, early-stage chronic kidney disease, refractory gynecological infections, minor anxiety and depression disorders. This clinical strategy involves a single treatment, since the EMITTAS procedure allows the patient to continue his/her own personal treatment at home by means of self-administration of the recorded aqueous system. A significant and long-lasting improvement has been reported, showing a potential beneficial use of this biophysical procedure in the management of common illnesses in an efficient, effective and personalized way. Data from recent studies suggest that aqueous systems may play a key role in providing the basis for recording, storing, transferring and retrieving clinically effective quanta of biological information. These features likely enable to trigger local and systemic self-regulation and self-regeneration potential of the organism.